Why truth matters - Benson, Ophelia; Stangroom, Jeremy (Continuum, 2006)
The authors present a philosophical case for the importance of truth that draws on writings by philosophers, anthropologists,poets, and scientists.
Includes bibliographical references (p. ) and index
Keywords: Waarheid; Truth; Wahrheit